Risk of Zika virus transmission in the Euro-Mediterranean area and the added value of building preparedness to arboviral threats from a One Health perspective - Camille Escadafal; Lobna Gaayeb; Flavia Riccardo; Elisa Pérez-Ramírez; Marie Picard; Maria Grazia Dente; Jovita Fernández-Pinero; Jean-Claude Manuguerra; Miguel-Ángel J; Silvia Declich; Kathleen Victoir; Vincent Robert (BMC, 2016)
Abstract In the alarming context of risk of Zika virus (ZIKV) transmission in the Euro-Mediterranean area, there is a need to examine whether capacities to detect, diagnose and notify ZIKV infections in the region are in place and whether ongoing capacity-building initiatives are filling existing gaps. The MediLabSecure network, created in 2014, comprises 55 laboratories of virology and medical entomology and 19 public health institutions in 19 countries in the Balkans, North-Africa, the Middle-East and the Black Sea regions. It aims to set up awareness, risk assessment, monitoring and control of emerging and re-emerging vector-borne viruses. We here examine the actions and strategies that MediLabSecure has been implementing and how they will contribute to the prevention and control of the ZIKV threat in the Euro-Mediterranean area. Capacity-building for arbovirus diagnostics is a major objective of the project and follows a methodological rather than disease-driven approach. This enables the implementation of laboratory trainings on techniques that are common to several arboviruses, including ZIKV, and putting into action appropriate diagnostic tools in the target region. Moreover, by its One Health approach and the interaction of its four sub-networks in human virology, animal virology, medical entomology and public health, MediLabSecure is fostering intersectoral collaboration, expertise and sharing of information. The resulting exchanges (methodological, communication and operational) across disciplines and across countries, dedicated research on intersectoral collaboration and increasing diagnostic capacities are providing new paths and tools to public health professionals to face emerging viral threats such as a ZIKV epidemic in the Euro-Mediterranean region.